Computer Aided Generation of Stylized Maps - Adabala, N.; Varma, M.; Toyama, K.; Toyama, Kentaro; Varma, Manik; Adabala, Neeharika (Computer Animation and Virtual Worlds, 2007)
Geographic maps have existed from early stages of human civilization. Various styles of visualizing the geographic information have evolved depending on the nature of information and the technology available for visualization. This has led to innumerable map styles. In this work we develop a technique to create maps by combining two-dimensional and three-dimensions information such that the resulting maps are both functional and aesthetically appealing. Our technique requires geographical information in vector form and aerial images as inputs. We use computer vision based approaches and user deﬁned inputs to augment the vector data with information that is required to create stylized maps. We deﬁne procedural graphics methods to generate a range of geographic elements that can be composed together into a stylized map. We demonstrate our technique by generating example maps of a region in Las Vegas.